2010
DOI: 10.1029/2009ja014827
|View full text |Cite
|
Sign up to set email alerts
|

Size and location of cusp diamagnetic cavities observed by Polar

Abstract: [1] We examine 6 years of cusp crossings by the Polar spacecraft to determine the size and solar wind dependence of cusp diamagnetic cavities (CDCs) and energetic particle events (CEPs). Both are frequently observed (about 50% of the time spent in the cusp). Neither shows a strong statistical dependence on upstream conditions beyond variations in the cusp itself. CEPs are found throughout the cusp, peaking near the magnetopause. CDCs are primarily found near local noon and close to the magnetopause, forming an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Though some observations agree with this gradual character for the inner transitions, for example Niehof et al (2010); Nykyri et al (2011a), others describe a much more rapid transition (Lavraud et al, 2002). This may be partly due to the dynamic nature of the cusp region, for instance Nykyri et al (2011b) have shown that some of the local fluctuations in plasma parameters within the CDC may be attributed to the reaction of the CDC to solar wind changes on relatively short timescales.…”
Section: Discussionmentioning
confidence: 80%
“…Though some observations agree with this gradual character for the inner transitions, for example Niehof et al (2010); Nykyri et al (2011a), others describe a much more rapid transition (Lavraud et al, 2002). This may be partly due to the dynamic nature of the cusp region, for instance Nykyri et al (2011b) have shown that some of the local fluctuations in plasma parameters within the CDC may be attributed to the reaction of the CDC to solar wind changes on relatively short timescales.…”
Section: Discussionmentioning
confidence: 80%
“…For example, the modeling of cusp soft electron precipitation in a coupled global geospace simulation requires a self‐consistent, dynamic, and accurate specification of the cusp area [e.g., Zhang et al , ]. In global MHD simulations, the area of the polar cusp can be defined by either the spatial extent of the diamagnetic depression [e.g., Niehof et al , ; Adamson et al , ; Walsh et al , ] or the simulated cusp plasma property, viz, relative density enhancement or parallel ion flux at high altitude. The three diagnostic methods give approximately the same area of the polar cusp, and only the results from the diamagnetic depression method are shown in the following section.…”
Section: Resultsmentioning
confidence: 99%
“…proposed local acceleration of particles in the cusp, particularly in diamagnetic cavities. Niehof et al (2010) showed a long-term association between observations of CEPs and cusp diamagnetic cavities; Walsh and Fritz (2011) presented electron observations consistent with local acceleration. Other studies have examined candidate mechanisms for such acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…Cusp passes and CEP events are based on the events from Niehof et al (2010), derived from the Polar satellite observations. Their derivation is briefly summarized here.…”
Section: Data Setsmentioning
confidence: 99%